A study of burpee jump and sit and reach in relation to the performance of free style wrestlers - Singh, V. (International Journal of Physiology, Nutrition and Physical Education, 2021)
The performance of players in various sports may be influenced by the anthropometric, physical and the physiological characteristics and may also aid in determining a suitable physique required for a sport. Methods: The physical variables such Burpee jump and Sit and reach as have been selected to assess the physical condition of the wrestler`s. A survey type study has been designed for descriptive analysis of wrestler`s physical characteristics Data was collected from 30 male wrestlers of each weight categories i.e. 57 kg, 61 kg, 65 kg, 70 kg and 74 kg. Results: The results revealed that the f-value of different weight category of variable Burpee jump and Sit and reach The f-value of the ANOVA came out to be 5.24 and 0.54 be, respectively (P<001) which was highly significant at 0.01 level of confidence. Conclusion: The correlation between performance score and physical variables among the players of 57, 61, 65, 70 and 74kg weight categories. The f-value Burpee Jump of the ANOVA came out to be 5.24, which was significant at 0.05 levels. The f-value (Sit and Reach) of the ANOVA came out to be 0.54, (P<001) which was not significant at 0.01. No significant relationship was found with performance score.